de Sitter vacua and supersymmetry breaking in six-dimensional flux compactifications - Buchmuller, W; Dierigl, M; Ruehle, F; Schweizer, J (American Physical Society, 2016)
We consider six-dimensional supergravity with Abelian bulk flux compactified on an orbifold. The effective low-energy action can be expressed in terms of N = 1 chiral moduli superfields with a gauged shift symmetry. The D -term potential contains two Fayet-Iliopoulos terms which are induced by the flux and by the Green-Schwarz term canceling the gauge anomalies, respectively. The Green-Schwarz term also leads to a correction of the gauge kinetic function which turns out to be crucial for the existence of Minkowski and de Sitter vacua. Moduli stabilization is achieved by the interplay of the D -term and a nonperturbative superpotential. Varying the gauge coupling and the superpotential parameters, the scale of the extra dimensions can range from the GUT scale down to the TeV scale. Supersymmetry is broken by F - and D -terms, and the scale of gravitino, moduli, and modulini masses is determined by the size of the compact dimensions.